Protection and promotion of immovable cultural heritage of local importance in the municipalities of Sandanski, Balchik, Kavarna and Garmen (Research Announcements "Heritage BG", 2025)
In the process of decentralisation of cultural heritage management in Bulgaria, it is a challenge for local authorities to develop and implement effective local policies for the protection and promotion of the immovable cultural heritage of local importance. To what extent do the municipalities manage to cope in the changed environment, what issues do they face, and what are the characteristics of the context in the municipalities – these are some of the questions that are analysed, based on focus group discussions, conducted within the ethnological study in the period May-June 2022 in four municipalities in Bulgaria – Sandanski, Balchik, Kavarna, and Garmen.  References:Denchev, Vasileva 2010: Denchev Stoyan, Sofia Vasileva, Darzhavnata politika za kulturno-istoricheskoto nasledstvo na Balgariya 1878 – 2009. Lektsii. Vtoro dopalnitelno i preraboteno izdanie. 2010. Sofia: Izdatelstvo “Za bukvite – O pismeneh”.Erolova 2023: Erolova, Yelis. Izsledvane na nedvizhimite kulturni tsennosti s kategoria „mestno znachenie“ v obshtina Balchik – Research Announcements. Bulletin ‘Heritage BG’, ed. Emmanuel Moutafov, No 5, 92–101.Kabakov 2020: Kabakov, Ivan. Pravna infrastruktura na profesionalnoto razvitie v oblastta na kulturnoto nasledstvo. In: Zakonodatelstvo i profesionalno razvitie v oblastta na kulturnoto nasledstvo. istoricheska rekonstruktsiya i aktualno sastoyanie v republika Balgariya. 2020 (Ed. Ivan Kabakov). Sofia: St. Kliment Ohridski University Press.Vladimirov 2021: Vladimirov, Zhelyu. Kulturnoto nasledstvo kato resurs za mestno razvitie. – Research Announcements. Bulletin ‘Heritage BG’, ed. Emmanuel Moutafov, No 1, 9–15.Vladimirov 2023: Vladimirov, Zhelyu. Kulturnoto nasledstvo kato resurs za mestno razvitie. Sofia: St Kliment Ohridski University Press.Hristova 2023: Hristova, Mina. Everyday Nationalism and Identity Narratives: The Case of the Built Environment in the Sandanski Municipality. – Research Announcements. Bulletin ‘Heritage BG’, ed. Emmanuel Moutafov, No 4, 74–88.LAWS Cultural Heritage Act 2009: Cultural Heritage Act 2009. Available at: https://lex.bg/laws/ldoc/2135623662 (22.11.2023)Law on protection and development of culture 1999: Law on protection and development of culture 1999. Available at: https://lex.bg/bg/laws/ldoc/2134664704Local Taxes and Fees Act 1998: Local Taxes and Fees Act 1998 Available at: https://lex.bg/laws/ldoc/2134174720 (22.11.2023)Patronage Act 2005: Patronage Act 2005. Available at: https://lex.bg/laws/ldoc/2135514206 (22.11.2023).Popcheva 2023: Popcheva, Julia. Unknown, Forgotten and (Re)discovered: A Possible New Life for Three Fortresses near the Town of Kavarna. – Research Announcements. Bulletin ‘Heritage BG’, ed. Emmanuel Moutafov, No 5, 92–101.
Keywords: immovable cultural heritage; local actors; local management; Bulgaria